Functional principles of baobab fruit pedicels – anatomy and biomechanics - Lautenschläger, Thea (Ann Bot, 2020)
BACKGROUND AND AIMS: Fruit pedicels have to deal with increasing loads after pollination due to continuous growth of the fruits. Thus, they represent interesting tissues from a mechanical as well as a developmental point of view. However, only a few studies exist on fruit pedicels. In this study, we unravel the anatomy and structural–mechanical relationships of the pedicel of Adansonia digitata, reaching up to 90 cm in length. METHODS: Morphological and anatomical analyses included examination of stained cross-sections from various positions along the stalk as well as X-ray microtomography and scanning electron microscopy. For mechanical testing, fibre bundles derived from the mature pedicels were examined via tension tests. For establishing the structural–mechanical relationships, the density of the fibre bundles as well as their cellulose microfibril distribution and chemical composition were analysed. KEY RESULTS: While in the peduncle the vascular tissue and the fibres are arranged in a concentric ring-like way, this organization shifts to the polystelic structure of separate fibre bundles in the pedicel. The polystelic pedicel possesses five vascular strands that consist of strong bast fibre bundles. The fibre bundles have a Young’s modulus of up to 5 GPa, a tensile strength of up to 400 MPa, a high density (>1 g cm(−3)) and a high microfibril angle of around 20°. CONCLUSIONS: The structural arrangement as well as the combination of high density and high microfibril angle of the bast fibre bundles are probably optimized for bearing considerable strain in torsion and bending while at the same time allowing for carrying high-tension loads.